Application of Adaptive QAM Modulation and Diversity Scheme for 30 GHz Cellular Communications under the Impact of Rain Attention in Indonesia - Gamantyo Hendrantoro; Achmad Mauludiyanto; Ninik D. Yundariani (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2007)
In millimeter-wave wireless cellular systems like Local Multipoint Distribution Services (LMDS) rain attenuation is an essential factor of performance degradation. It can cause signal outages and poor quality of signal reception. To mitigate the problem, a combination of diversity and adaptive modulation is proposed. To investigate the impact of the use of these techniques, a simulation is performed for a 30 GHz cellular system to obtain SNR (signalto- noise ratio), diversity gain, modulation level and BER (bit error rate). Analysis of the implementation of the combined techniques is accomplished by taking into account such factors as length of links and the combining method Simulation results show that diversity can improve the overall system SNR. Diversity gain of up to 15 dB can be achieved on two 4-km converging links at 0.01% outage probability when maximal-ratio combining (MRC) is used. For systems with luxurious link design for which the clearsky SNR is more than 30 dB, as considered in this paper, diversity and adaptive modulation do not significantly contribute to improvement of achievable transmission rate and BER performance. However, for systems with lower values of clear-sky SNR, use of both techniques will be more worthwhil.